Efektifitas Strategi Bauran Pemasaran dalam Meningkatkan Pengunjung pada Hotel Dalwa Syariah Bangil Pasuruan ditinjau dari Etika Bisnis Islam - Himmah, Faiqotul; Mundir, Abdillah; Farida, Alimatul (Jurnal Iqtisaduna, 2024)
Marketing strategy is a comprehensive plan that directs a company’s marketing efforts to achieve its goals. Consists of seven elements: product, price, place, promotion, people, process, and physical evidence. Islamic business ethics is a set of moral principles that guide business activities, which originate from the Koran and Hadith. Business ethics in Islam emphasizes honesty, transparency, fairness, trustworthiness, and generosity. This research uses a qualitative approach which involves collecting data through observation, interviews and document analysis. Research is carried out in a natural context and is exploratory in nature. Research Results Dalwa Syariah Hotel has implemented various marketing strategies, including market segmentation and marketing mix strategies. This hotel is collaborating with Online Travel Agents, Corporate Clients, Governance and Travel to increase the number of visitors. The hotel marketing mix strategy, which includes product, price, place, promotion, people, process and physical evidence, is in line with Islamic business ethics.